Analysis of Bioterrorism Studies on Lung Health: A Meta-Analysis - Nutari, Hasbi; Yessy Susanty Sabri (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Bioterrorism, the use of biological agents to cause mass harm, poses a significant threat to lung health. This meta-analysis aims to evaluate the impact of bioterrorism on lung health, identifying the most frequently used agents, clinical manifestations, and policy implications. Methods: A comprehensive literature search was conducted on PubMed, Scopus, and Web of Science databases from 2018 to 2024. Studies reporting the impact of bioterrorist attacks on lung health were included. Epidemiological, clinical, and interventional data were extracted and analyzed using random effects models. Results: Twenty studies met the inclusion criteria, covering a total of 15,482 participants. The most common bioterrorism agent was Bacillus anthracis (43.5%), followed by Yersinia pestis (21.7%) and Francisella tularensis (17.4%). The most frequently reported clinical manifestations were pneumonia (78.3%), acute respiratory failure (39.1%), and sepsis (26.1%). Mortality rates vary from 5% to 35%, depending on the agent and intervention administered. Conclusion: Bioterrorism poses a serious threat to lung health, causing significant morbidity and mortality. Pneumonia, acute respiratory failure, and sepsis are the most common clinical manifestations. It is important to improve preparedness, early detection, and clinical management to reduce the impact of bioterrorist attacks.